Pengaruh Struktur Modal, Profitabilitas dan Keputusan Investasi Terhadap Nilai Perusahaan yang Dimoderasi Ukuran Perusahaan. - Amelia, Arliza; Kadir, Abdul; Syahdan, Saifhul Anuar; Boedi, Soelistijono (Owner : Riset dan Jurnal Akuntansi, 2024)
The purpose of this study was to analyze and find real evidence regarding capital structure, profitability and investment decisions on firm value moderated by company size which may or may not affect the three independent variables on firm value. This research uses purposive sampling method. This study uses food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2018-2022, obtained 27 companies as a population with the number of samples used in the study of 135. The data analysis used is regression analysis and classical assumptions, and hypothesis testing is also carried out using multiple linear regression analysis and moderation regression testing. The results of this study indicate that capital structure, profitability and investment decisions have a positive effect on firm value. Company size as a moderating variable is able to moderate (weaken) the effect of capital structure on firm value, company size is also able to moderate (strengthen) the effect of profitability on firm value and company size is not able to moderate (weaken or strengthen) the effect of investment decisions on firm value. Keywords: Capital structure, profitability, investment decision, firm value, company size